'Rushing Remand'? Pretrial Detention and Bail Decision Making in England and Wales. Issue 1 (17th September 2020) - SMITH, TOM
Abstract: Deprivation of liberty as part of the criminal process is always a significant step, and arguably even more so when the person so deprived has not yet been convicted of an offence. Remand decision making – that is, granting bail or requiring detention of a defendant prior to trial – in the courts of England and Wales is a common and important part of modern criminal procedure, yet has been under‐examined in the last two decades. This article presents some of the findings of the first empirical study of remand law and practice in this jurisdiction in many years. It concludes that, notwithstanding that the rate of pretrial detention is comparatively low and practice is broadly in line with domestic and regional standards, there remain significant issues – particularly in relation to the time spent on such decisions and the information provided to courts when considering remands on bail or in custody.